Efficacy of Laparoscopic-Guided Transversus Abdominis Plane Block versus Standard Analgesia for Postoperative Pain Control in Laparoscopic Cholecystectomy - Zulfiqar, Ghazanfar; Anwar, Muhammad Imran; Jameel, Zaigham; Ghazanfar, Saqlain; Khan, Muzammil; Tariq, Talha (Biological and Clinical Sciences Research Journal, 2025)
The management of postoperative pain following laparoscopic cholecystectomy remains a clinical challenge. While systemic analgesics are routinely used, they may be associated with suboptimal relief and adverse effects. The laparoscopic-guided Transversus Abdominis Plane (TAP) block has emerged as a promising regional technique for effective postoperative analgesia. Objectives: To compare the efficacy of laparoscopic-guided TAP block versus standard systemic analgesia for postoperative pain control in patients undergoing laparoscopic cholecystectomy. Methodology: A prospective, randomized controlled trial conducted at the Department of Surgery Sheikh Zayed Hospital, Lahore, from March 2023 se April 2024. A total of 140 patients undergoing elective laparoscopic cholecystectomy were randomly divided into two equal groups: TAP block group (n=70) and standard analgesia group (n=70). The TAP block was administered under direct laparoscopic guidance at the end of surgery. Postoperative pain was assessed using the Visual Analogue Scale (VAS) at 2, 4, 8, 12, and 24 hours. Secondary outcomes included time to first analgesic request, total 24-hour tramadol consumption, frequency of rescue analgesia, and patient satisfaction. Results: VAS scores were significantly lower at all intervals in the TAP group (p < 0.001). The mean time to first analgesic request was longer (6.8 ± 2.5 vs 3.2 ± 1.7 hours), and tramadol consumption was lower (84.2 ± 21.4 mg vs 137.5 ± 30.8 mg) in the TAP group (p < 0.001). Patient satisfaction was also significantly higher (p < 0.001). Conclusion: Laparoscopic-guided TAP block provides superior postoperative analgesia, delays the need for rescue analgesics, reduces opioid use, and improves patient satisfaction compared to standard analgesia.